Don Issac Abravanel : an intellectual biography - Cohen Skalli, Cedric (Tauber Institute for the Study of European Jewry series (Unnumbered), 2021)
"An intellectual biography of Don Isaac ben Judah Abravanel, a 15th century Portuguese rabbi, scholar, Bible commentator, philosopher, and statesman"--